PENDIDIKAN AKHLAK TERHADAP ANAK DALAM BUKU ORANGTUANYA MANUSIA KARYA MUNIF CHATIB - Wulansari Wulansari (Tarbiya Islamica, 2013)
The research was conducted because of the researcher's interest in examining more deeply the work of Munif Chatib. This study aims to; (1) Knowing and describing teaching ethics in moral education for children in Munif Chatib's Human Parents Book. (2) Knowing and describing the special methods of moral education for children in Munif Chatib's parents book Manusia by Munif Chatib. (3) Knowing and describing the relevance of the concept of child education by Munif Chatib with Islamic child education. The research method used is data collection techniques and data analysis techniques, data validity checking techniques which include triagulation. The results of this research can be concluded that: 1) Ethics of teaching in the moral education of children in the human parents book by Munif Chatib, including; first, the lack of equal distribution of education. National education has not been able to guarantee equitable distribution of educational opportunities for every prospective student, either in the slow learner category or slow in receiving knowledge information, especially for children with special needs. Second, the lack of parental attention to children. 2) The special method of moral education for children in the book Human by Munif Chatib's parents, child education is an effort that is oriented towards student growth and development not only academic achievement and protects and guarantees dignified and comprehensive human beings from all human intelligence (children). 3) The relevance of the concept of Munif Chatib's children's education with Islamic children's education is; a) the essence of his Islamic children's education, that children are the work of the Supreme Lord, entrusted by Allah SWT to parents. b) children born with a divine nature can be educated, because children have the potential to become a pleasant dream, when given a good education, and vice versa, c) make the family the first child's education which is directed towards religious cultivation, aqidah, worship, and based morals. Al-Qur'an and the words of the Prophet Muhammad. d) teachers who always try to educate based on a sincere attitude. The thought of Islamic children's education, he strives to provide the best education for children both in the family and school environment, which is based on Islamic children's education.